DIFFERENTIAL CLINICAL INDICATORS IN CHILDREN WITH ASPERGER’S AND KANNER’S SYNDROMES - Doniyorova F.A. (Central Asian Journal of Medicine, 2025)
Autism spectrum disorder (ASD) encompasses a wide range of neurodevelopmental syndromes, most notably Asperger’s syndrome (AS) and Kanner’s syndrome (KS). Despite overlapping characteristics, key clinical differences exist between these syndromes. This study investigates differential clinical indicators in 240 children aged 3–11 years, categorized into AS and KS groups. Emphasis was placed on speech development, cognitive functioning, comorbidity profiles, and social behaviors. The results support the necessity for a refined diagnostic approach and tailored therapeutic strategies.